Chapter Enrichment of the Medical Vocabulary in the Greek-Speaking Medieval Communities of Southern Italy The Lexica of Plant Names - Bouras-Vallianatos, Petros (Istanbul Research Institute, 2018)
medical vocabulary; Greek speaking; medieval communities; Southern Italy; plant names